A Path Toward Sustainable Development Along the Belt and Road. (25th September 2021) - Lorenzo, Johanna Aleria P
ABSTRACT: The article scrutinizes the purported synergies between the Belt and Road Initiative (BRI) and the United Nations (UN) 2030 Agenda for Sustainable Development by evaluating the transnational legal order regulating environmental and social impacts of BRI economic activities. From the perspective of international law and sustainable development, three problematic features are identified. First, the bilateral character of agreements between China and BRI-participating States produces fragmented and variable sustainability standards. Second, the informality of State-to-State arrangements often hinder parliamentary and public deliberation in host States. Lastly, BRI decision-making processes restrict non-State actor participation and thereby disregard the very communities harmed by infrastructure projects. To clear its path to sustainability and bring it closer to the UN agenda, BRI's legal and regulatory framework must become multilateral, transparent, and inclusive. The proposal entails bringing to fore the relevant background international legal norms, especially on environmental, labor, and human rights protection, and consolidating them in a framework agreement that sets minimum sustainability safeguards for transboundary economic activities like foreign-funded infrastructure projects. Reforms are imperative because the subject matter of the Initiative requires international cooperation and involves not only the economic, environmental, and social concerns of two States but also implicates the goals and interests of the international community.